Upgrade of BL‐5C as a highly automated macromolecular crystallography beamline at Pohang Light Source II. (5th February 2021) - Jeong, Jae-Hee; Eo, Cheolsoo; Kim, Hyo-Yun; Kim, Jin-Hong; Lee, Chae-Soon; Choi, Hyeong-Joo; Kim, Yeon-Gil
Abstract : BL‐5C, a macromolecular crystallography beamline, at PLS‐II has been upgraded to support automated and high‐throughput data collection. Abstract : BL‐5C is an in‐vacuum undulator beamline dedicated to macromolecular crystallography (MX) at the 3 GeV Pohang Light Source II in Korea. The beamline delivers X‐ray beams with a focal spot size of 200 µm × 40 µm (FWHM, H × V) over the energy range 6.5–16.5 keV. The measured flux is 7 × 10 11  photons s −1 at 12.659 keV through an aperture size of 50 µm. The experimental station is newly equipped with the photon‐counting detector EIGER 9M, the multi‐axis micro‐diffractometer MD2, and a robotic sample changer with a high‐capacity dewar. These instruments enable the operation of this beamline as an automated MX beamline specialized in X‐ray fragment screening. This beamline can collect more than 400 data sets a day without human intervention, and a difference map can be automatically calculated by using the data processing pipeline for ligand or fragment identification.